Pengembangan Bahan Ajar Etnomatematika Bernuansa Baju Pengantin Adat Betawi - Tamara Rizkyh; Desi Setiyadi; Meilina (Jurnal Elementaria Edukasia, 2023)
This research aims to develop an ethnomathematics teaching material with nuances of Betawi traditional wedding dresses. as a means to improve understanding of geometry for fourth grade students in elementary schools (SD). In the world of education which is increasingly growing and developing, education about culture is increasingly decreasing because it is being replaced by foreign culture. The research is based on the lack of relevant and contextual teaching materials in this material so that it has the aim of distributing ethnomathematics teaching material with nuances of traditional Betawi wedding dresses by applying flat shape material in elementary schools. The research respondents were 32 class IV students at SDN Petir 4 Tangerang City. This research uses the method, Research And Development (R and D), developing a 4-D model. The results of the resulting research and product development show that (1) Ethnomatics teaching materials with traditional Betawi wedding dress nuances can significantly improve students' understanding of geometry, (2) the validity of ethnomatics teaching materials is demonstrated by the results of the geometry material expert test and media expert test of 4.53 with a very worthy category